2005
DOI: 10.1227/01.neu.0000163688.17385.9b
|View full text |Cite
|
Sign up to set email alerts
|

Remote Cerebellar Hemorrhage after a Spinal Surgery Complicated by Dural Tear: Case Report and Literature Review

Abstract: Although it is an extremely rare complication, remote cerebellar hemorrhage should be kept in mind as a possible complication of spinal surgery, especially in operations complicated by dural tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
61
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 9 publications
2
61
0
4
Order By: Relevance
“…Failure to achieve watertight dural closure not only can increase the incidence of spinal headache, nausea, and vomiting immediately after surgery, 23,28,33 but may also predispose patients to more serious postoperative complications such as CSF leakage, CSF-cutaneous fistula, pseudomeningocele, wound infection, meningitis, and even intracranial hemorrhage. 1,14,17 Some methods of MIS dural closure have been described in the literature. Chou et al 4 reported a technique for MIS primary dural repair using a micropituitary rongeur as the needle holder in combination with a laparoscopic knot pusher commonly used in arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to achieve watertight dural closure not only can increase the incidence of spinal headache, nausea, and vomiting immediately after surgery, 23,28,33 but may also predispose patients to more serious postoperative complications such as CSF leakage, CSF-cutaneous fistula, pseudomeningocele, wound infection, meningitis, and even intracranial hemorrhage. 1,14,17 Some methods of MIS dural closure have been described in the literature. Chou et al 4 reported a technique for MIS primary dural repair using a micropituitary rongeur as the needle holder in combination with a laparoscopic knot pusher commonly used in arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…While the focus of our report is on supratentorial procedures, it should be noted that acute loss of CSF after spinal procedures may also cause the same subarachnoid bleeding pattern in the cerebellum. 13 In our case, RCH was observed after a large amount of supratentorial CSF fluid was drained.…”
Section: Discussionmentioning
confidence: 53%
“…Since then, eight more cases of patients with cerebellar haematoma after spinal operations have been published [5 (2 cases), 7,8,12,14,20,21].…”
Section: Discussionmentioning
confidence: 99%